Super-Resolution Microscopy Reveals Presynaptic Localization of the ALS/FTD Related Protein FUS in Hippocampal Neurons - Schoen, Michael; Reichel, Jochen M.; Demestre, Maria; Putz, Stefan; Deshpande, Dhruva; Proepper, Christian; Liebau, Stefan; Schmeisser, Michael J.; Ludolph, Albert C.; Michaelis, Jens; Boeckers, Tobias M. (Frontiers in Cellular Neuroscience, 2016)
Fused in Sarcoma (FUS) is a multifunctional RNA- / DNA-binding protein, which is involved in the pathogenesis of the neurodegenerative disorders amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). A common hallmark of these disorders is the abnormal accumulation of mutated FUS protein in the cytoplasm. Under normal conditions FUS is confined to the nuclear compartment, in neurons however, additional somatodendritic localization can be observed. In this study, we carefully analyzed the subcellular localization of endogenous FUS at synaptic sites of hippocampal neurons which are among the most affected cell types in frontotemporal dementia with FUS pathology. We could confirm a strong nuclear localization of FUS as well as its prominent and widespread neuronal expression throughout the adult and developing rat brain, particularly in the hippocampus, the cerebellum and the outer layers of the cortex. Intriguingly, FUS was also consistently observed at synaptic sites as detected by neuronal subcellular fractionation as well as by immunolabeling. To define a pre- and / or postsynaptic localization of FUS, we employed super-resolution fluorescence localization microscopy. FUS was found to be localized within the axon terminal in close proximity to the presynaptic vesicle protein Synaptophysin1 and adjacent to the active zone protein Bassoon, but well separated from the postsynaptic protein PSD-95. Having shown the presynaptic localization of FUS in the nervous system, a novel extranuclear role of FUS at neuronal contact sites has to be considered. Since there is growing evidence that local presynaptic translation might also be an important mechanism for plasticity, FUS - like the fragile X mental retardation protein FMRP - might act as one of the presynaptic RNA-binding proteins regulating this machinery. Our observation of presynaptic FUS should foster further investigations to determine its role in neurodegenerative diseases such as ALS and FTD.